Модельні характеристики та спортивно-значущі якості у спортивній боротьбі - Грдзелідзе, Сергій Ріпатович; Курій, Олена Володимирівна (Center of modern pedagogy "Learning without boarders", Canada, 2017)
У статті висвітлені результати проведених досліджень щодо виявлення основних модельних характеристик у спортивній боротьбі. Виявлені показники виразності психологічних властивостей, необхідних для вищих досягнень у спортивній боротьбі. Також виявлені спортивно-значущі якості для спортсменів-борців вільного стилю. Наведені характеристики індивідуально-психологічних особливостей спортсменів-борців з різним спортивним досвідом і спортивною кваліфікацією.

The article highlights the results of research to identify the main characteristics of the model in wrestling. Identified indicators of severity of psychological properties required for higher achievements in wrestling. Sports-significant qualities for free-style wrestlers are also revealed. The characteristics of individual psychological characteristics of athletes-fighters with different sports experience and sports qualification are given.
Model characteristics and sports-significant qualities in wrestling
Keywords: психологічні властивості; фізична культура; спорт; вільна боротьба; model characteristics; severity of psychological properties; sports and important quality wrestling